Massive and efficient encapsulation of single cells in monodisperse droplets and collagen–alginate microgels using a microfluidic device - Liu, Dan; Xuanyuan, Tingting; Liu, Xufang; Fu, Wenzhu; Liu, Wenming (Frontiers in Bioengineering and Biotechnology, 2023)
Single cell manipulation is the key foundation of life exploration at individual cell resolution.Constructing easy-to-use, high throughput, and biomimetic manipulative tools for efficient single cell operation is quite necessary. Here, a facile and efficient encapsulation of single cells relying on massive and controllable production of droplets and collagen-alginate microgels using a microfluidic device is presented. High monodispersity and geometric homogeneity of both droplet and microgel generation were experimentally demonstrated based on the wellinvestigated microfluidic fabricating procedure. The reliable capability of the microfluidic platform for controllable, high throughput, and improved single cell encapsulation in monodisperse droplets and microgels was confirmed too. A single cell encapsulation rate up to 33.6% was achieved based on the established microfluidic operation. The introduction of stromal material in droplets/microgels for the encapsulation provided single cells in vivo simulated microenvironment. The single cell operation achievement offers a methodological approach for developing simple and miniaturized devices to perform single cell manipulation and analysis in a high throughput and microenvironment-biomimetic manner. We believe that it holds great potential for applications in precision medicine, cell microengineering, drug discovery, and biosensing.